2015
DOI: 10.4314/jasem.v18i4.3
|View full text |Cite
|
Sign up to set email alerts
|

Antifeedant and Toxic Effect of Crude Extract from <i>Flourensia oolepis</i> and their Impact on Nutritional Parameters of <i>Helicoverpa gelotopoeon</i>

Abstract: Botanical insecticides are one of the environmentally acceptable options for pest management. Extract of Flourensia oolepis (known as chilca), a plant endemic to the province of Córdoba, Argentina, has shown insecticidal activity. The aim of this work was to study the effect of crude extract of this F. oolepis on the nutritional parameters of Helicoverpa gelotopoeon, a polyphagous species recently reported as one of the most serious pests of chickpea. Choice tests were conducted using different doses of extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…In a recent paper, we have demonstrated that its natural occurrence is restricted only to some Flourensia species, strictly FC, FO and F. fiebrigii, being absent in F. hirta, F. riparia and F. niederleinii, and in 37 of the most representative co-occurring species of FC and FO [15]. The composition of the resins from the genus Flourensia has revealed the presence of other phytotoxic compounds, as in F. cernua [16] and in FO [17]- [19]. Other resin components in Flourensia spp.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper, we have demonstrated that its natural occurrence is restricted only to some Flourensia species, strictly FC, FO and F. fiebrigii, being absent in F. hirta, F. riparia and F. niederleinii, and in 37 of the most representative co-occurring species of FC and FO [15]. The composition of the resins from the genus Flourensia has revealed the presence of other phytotoxic compounds, as in F. cernua [16] and in FO [17]- [19]. Other resin components in Flourensia spp.…”
Section: Introductionmentioning
confidence: 99%